2003
DOI: 10.1103/physrevc.68.054611
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-spin isomers in proton induced reactions at100500MeVonTa181

Abstract: Cross sections for production of a broad variety of high-spin isomers, i.e., 177 Hf m2 ͑37/2 − ͒, 179 Hf m2 ͑25/2 − ͒, 177 Lu m ͑23/2 − ͒, 180 Hf m ͑8 − ͒, and 178 Ta m ͑7 − ͒ from 181 Ta targets irradiated with 100, 145, 200, 350, and 500 MeV protons have been measured by off-line ␥-spectroscopy. A radiochemical procedure was used to achieve high sensitivity. Isomer ratios in products ranging down to 10 −3 were based on experimentally measured and theoretically calculated cross sections. It was demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In [41], the isomeric ratios of the reaction products 181 Ta(p, p3n) 178m,g Ta were obtained at proton energies of 100, 145, 200, 350, and 500 MeV using by off-line γ-spectroscopy. It is shown that the obtained isomeric ratios are constant and close to d(E) ∼ 0.37-0.38 at 100-500 MeV.…”
Section: Isomeric Ratio D(e γMax ) Of the Reaction Products Of Thementioning
confidence: 99%
“…In [41], the isomeric ratios of the reaction products 181 Ta(p, p3n) 178m,g Ta were obtained at proton energies of 100, 145, 200, 350, and 500 MeV using by off-line γ-spectroscopy. It is shown that the obtained isomeric ratios are constant and close to d(E) ∼ 0.37-0.38 at 100-500 MeV.…”
Section: Isomeric Ratio D(e γMax ) Of the Reaction Products Of Thementioning
confidence: 99%
“…This is not very surprising, recalling that the σ m /σ g ratio therefrom changes rather slowly with the proton energy [5,6], conˇrmed later in Ref. [14].…”
Section: Cross-sectionsmentioning
confidence: 60%
“…Finally, the contribution of the electronuclear interaction was found to be about 0.13 Y phr , where Y phr was the yield determined before for the photonuclear reaction. The calculated productivity under optimum conditions was then corrected to include both secondary and electron-induced processes, giving a total yield: Y opt = 3.2 • 10 9 atoms/(s • 100 µA) (14) for the 178m2 Hf isomer. This is about 8 times lower than the yield achieved at Los Alamos with a proton beam of the same current.…”
Section: Optimization Of Productivitymentioning
confidence: 99%
“…As a result, the primary products originating from reaction remnants, have a wide range of angular momenta and excitation energies. The comparison of the measured isomer cross section ratios with calculations within different statistical models [2,3] helps to estimate the spin associated with the reaction products, produced in different exit channels.…”
Section: Introductionmentioning
confidence: 99%